An ecological dynamics approach to skill acquisition: Implications for development of talent in sport - Davids, K.; Araújo, D.; Vilar, L.; Renshaw, I.; Pinder, R. (Talent Development & Excellence, 2013)
This paper proposes how ecological dynamics, a theory focusing on the performer-environment relationship, provides a basis for understanding skill acquisition in sport. From this perspective, learners are conceptualized as complex, neurobiological systems in which inherent self-organisation tendencies support the emergence of adaptive behaviours under a range of interacting task and environmental constraints. Intentions, perceptions and actions are viewed as intertwined processes which underpin functional movement solutions assembled by each learner during skill acquisition. These ideas suggest that skill acquisition programmes need to sample information from the performance environment to guide behaviour in practice tasks. Skill acquisition task protocols should allow performers to use movement variability to explore and create opportunities for action, rather than constraining them to passively receiving information. This conceptualisation also needs to characterize the design of talent evaluation tests, which need to faithfully represent the perception-action relationships in the performance environment. Since the dynamic nature of changing task constraints in sports cannot be predicted over longer timescales, an implication is that talent programmes should focus on developing performance expertise in each individual, rather than over-relying on identification of expert performers at specific points in time.